THE DESCRIPTION OF CHARACTER VALUES IN ENGLISH LEARNING TOWARDS THE ELEVENTH GRADE STUDENTS OF SMA SARASWATI 1 TABANAN - Gusti Ayu Gede Sukraningsih (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
This research purposed to describe character values in English learning to the eleventh-grade students at SMA Saraswati 1 Tabanan. The subjects of this research were an English teacher and 24 students. The techniques used to collect the data were observation, interview, and documentation. The data obtained were analysed by using qualitative data analysis. The result of this research showed that: (1) Character education was implemented in learning process, (2) Character education in this research was inserted by strategy of micro character development including teaching and learning in the classroom. Key words: Character Education, Implementation, English Learning